2004
DOI: 10.1007/s00330-003-1946-0
|View full text |Cite
|
Sign up to set email alerts
|

T2 relaxation time analysis in patients with multiple sclerosis: correlation with magnetization transfer ratio

Abstract: The aim of the current study was to perform T2 relaxation time measurements in multiple sclerosis (MS) patients and correlate them with magnetization transfer ratio (MTR) measurements, in order to investigate in more detail the various histopathological changes that occur in lesions and normal-appearing white matter (NAWM). A total number of 291 measurements of MTR and T2 relaxation times were performed in 13 MS patients and 10 age-matched healthy volunteers. Measurements concerned MS plaques (105), NAWM (80),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 29 publications
3
42
1
2
Order By: Relevance
“…10-12. We found that enhancing lesions had shorter T2 than nonenhancing lesions but longer T2 than NAWM. This finding is consistent with those in other studies, 11,19 whereas some early studies on relaxation times in MS lesions showed a longer T2 in acute than in chronic lesions. 20 However, looking at the original studies, Larsson et al 21 did not find a difference in T1 and T2 measurements between acute and chronic plaques, but a tendency toward a slight increase in T1 and T2 in the acute plaques and a very high T2 value in the center of the plaque at a later stage.…”
Section: Discussionsupporting
confidence: 93%
“…10-12. We found that enhancing lesions had shorter T2 than nonenhancing lesions but longer T2 than NAWM. This finding is consistent with those in other studies, 11,19 whereas some early studies on relaxation times in MS lesions showed a longer T2 in acute than in chronic lesions. 20 However, looking at the original studies, Larsson et al 21 did not find a difference in T1 and T2 measurements between acute and chronic plaques, but a tendency toward a slight increase in T1 and T2 in the acute plaques and a very high T2 value in the center of the plaque at a later stage.…”
Section: Discussionsupporting
confidence: 93%
“…The main etiologies of increased water concentration in central nervous parenchyma are inflammatory processes, edema, demyelination, gliosis, or neuronal loss. [10][11][12] A higher mean value of T2 relaxation time was observed in the NAWM and CC of the test group in our study, compared with the control group, demonstrating higher water concentration in these regions. The cause of this increased water concentration is thought to be axonal loss (with concomitant myelin sheath loss) and gliosis, secondary to TBI.…”
Section: Discussionsupporting
confidence: 44%
“…[16,92] Previous reports of relaxation measurements in MS lesions have shown variable result. Some findings are in line with our study, with shorter T2 in enhancing lesions and longer T2 in non-enhancing lesions [93], and longer T2 in enhancing lesions compared to NAWM [94]. An early study reported a decrease in T1 and T2 over time in acute brain stem lesions.…”
Section: Paper IIsupporting
confidence: 92%